Therapeutic drug monitoring of benznidazole and nifurtimox: a systematic review and quality assessment of published clinical practice guidelines (2017)
The pharmacological management of adults with chronic-phase Chagas disease is challenging despite it being the recent focus of extensive research. One of the challenges in the current clinical practice guidelines (CPGs) landscape is the existence of non-evidence-based recommendations for the use of laboratory tests in treatment monitoring. This study aimed to systematically assess the quality and consistency of recommendations of CPGs on the pharmacological management of adults with chronic-phase Chagas disease. Systematic literature searches were conducted in MEDLINE, EMBASE, SciELO and Google to identify all published CPGs relevant to the pharmacological management of Chagas disease, between January 2010 and March 2016. Three independent reviewers assessed the quality of each CPG using the Appraisal of Guidelines Research and Evaluation (AGREE) II instrument. A total of five CPGs were included and the overall quality of the guidelines for therapeutic drug monitoring of Chagas disease was moderate-to-low. There was considerable variation in the quality of the CPGs across the AGREE II domains. The domains of scope/purpose, stakeholder involvement, and clarity of presentation were rated well, and the domains of applicability and editorial independence received poor ratings. This review showed that the methodological quality of CPGs for Chagas disease was generally inappropriate, and there was no explicit link between the best available evidence and current recommendations.